Effects of rare earth oxide La2O3 on microstructure and properties of Al2O3/Al composites. (May 2015) - Wang, T. G.; Liang, Q. C.; Qin, Q.
<x content-type="archive" xml:space="preserve">Abstract</x> Al2O3/Al composite-doped La2O3 was processed by a powder metallurgy process, and the effects of the addition of rare earth La2O3 on the microstructures and mechanical properties were investigated by scanning electron microscopy and universal properties tests. The refinement mechanism of the rare earth oxide was investigated as well. It has found that the addition of La2O3 increased the density of the sintered Al2O3/Al composite and the matrix grains were significantly refined. The addition of La2O3 showed a remarkable improvement on the compression strength, which was up to more than 150% higher than that of materials not doped with rare earth oxides.